A Splice Site Variant of CDK12 and Breast Cancer in Three Eurasian Populations - Bogdanova, Natalia V.; Schürmann, Peter; Valova, Yana; Dubrowinskaja, Natalia; Turmanov, Nurzhan; Yugay, Tatyana; Essimsiitova, Zura; Mingazheva, Elvira; Prokofyeva, Darya; Bermisheva, Marina; Khusnutdinova, Elza; Dörk, Thilo (Frontiers in Oncology, 2019)
CDK12 is a member of the cyclin-dependent kinase family that acts as regulator of DNA damage response gene expression. A c.1047-2A>G splice site variant of the CDK12 gene was recently reported to strongly associate with hereditary breast and ovarian cancer in patients of Tatar ethnic origin. To gain more insight into the potential risk and the population spread of the c.1047-2A>G variant, we have genotyped three breast cancer case-control series of Tatar, Bashkir and Kazakh ethnicity. We identified c.1047-2A>G in 6/155 cases and 12/362 controls of Tatar ancestry, 0/96 cases and 9/189 controls of Bashkir ancestry, and 1/131 cases and 0/154 controls of Kazakh ancestry (Mantel-Haenszel odds ratio 0.72, 95% CI 0.30-1.70, p= 0.45). Consistent with the absence of a large effect, bioinformatic analyses predicted that c.1047-2A>G modulates alternative splicing of a NAGNAG sequence rather than constituting a loss-of-function allele, and RT-PCR analyses of c.1047-2A>G heterozygous lymphocytes verified the usage of the predicted alternative acceptor site. Our study confirms a high prevalence of CDK12*c.1047-2A>G in the Tatar and Bashkir population but excludes a role as a clinically actionable high-risk breast cancer mutation.